2020
DOI: 10.1088/1361-648x/ab5326
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Griffiths like phase, unconventional dual glassy states, giant exchange bias effects and its correlation with its electronic structure in Pr2−x Sr x CoMnO6

Abstract: Electronic structure, electrical transport, dc and ac magnetization properties of the hole substituted (Sr 2+ ) partially B-site disordered double perovskite Pr 2-x Sr x CoMnO 6 system have been investigated.Electronic structure was probed by employing X-ray photoemission spectroscopy (XPS) measurements. The study suggested the presence of mixed valence states of the B-site ions (Co 2+ /Co 3+ and Mn 3+ /Mn 4+ ) with significant enhancement of the average oxidation states due to hole doping. The mere absence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 99 publications
3
28
0
Order By: Relevance
“…In the case of LSCMFO, since the θ CW obtained from the CW fitting of the PM region lies far below the FM ordering T, we have chosen T R C = T C , yielding λ = 0.64. This value lies within the range found for resembling DP compounds [13,17,26,41]. The lattice distortions and the cationic disorder at the TM ionsite, intrinsic to the R 3c space group, certainly play a part in the GP.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In the case of LSCMFO, since the θ CW obtained from the CW fitting of the PM region lies far below the FM ordering T, we have chosen T R C = T C , yielding λ = 0.64. This value lies within the range found for resembling DP compounds [13,17,26,41]. The lattice distortions and the cationic disorder at the TM ionsite, intrinsic to the R 3c space group, certainly play a part in the GP.…”
Section: Resultssupporting
confidence: 78%
“…Since the Mn 4+ ionic radius is smaller than that of Fe 3+ [16], the incorporation of Fe in the system is expected to expand the lattice, as observed. On the other hand, previous studies have also indicated a Co 2+ /Co 3+ mixed valence state in LSCMO and resembling compounds [12,15,17]. Therefore, the introduction of Fe 3+ in place of Mn 4+ induced the Co ions to a trivalent state in order to ensure the charge balance, which prevents a larger increase of the unit cell volume.…”
Section: Resultsmentioning
confidence: 94%
“…[ 65 ] Moreover, according to the Goodenough–Kanamori [ 67 ] rule, the empty Mn 3+ /Mn 4+ orbital and the full Fe 3+ /Fe 2+ orbital should have a strong FM interaction. There are different types of superexchange couplings according to the Goodenough–Kanamori rules combinations in these compounds: [ 84,85 ] 1) Mn 3+ −O 2− −Mn 3+ FM/AFM; 2) Fe 3+ −O 2− −Fe 3+ , Mn 4+ −O 2− −Mn 4+ strong AFM; 3) Fe 3+ −O 2− −Mn 3+ AFM/FM; 4) Fe 2+ −O 2− −Mn 4+ FM.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of ordered perovskite, the interactions between transitional metal ions are mediated by the B-O-B ′ -O-B long-range order [8,9]. Notably, at the Bsite, achieving an ordered arrangement of transition metal ions is challenging due to the presence of antisite disorder (ASD) [10,11]. This ASD is an imperfection created by interchanging the position of the transition metal ions in ordered structures [10,11].…”
Section: Introductionmentioning
confidence: 99%